A novel and effective passive cooling strategy for photovoltaic panel. (July 2021) - Nižetić, Sandro; Jurčević, Mišo; Čoko, Duje; Arıcı, Müslüm
Abstract: This paper reports experimental work related to passively cooled free-standing silicon photovoltaic panels (PV) in different cooling configurations with a considered utilization of phase change materials (PCM). The PV panels (20Wp) were examined in typical Mediterranean climate conditions during several months of field monitoring. The focus of the research was to reconsider the usually conventional applied passive cooling approach for PVs in cases when the PV panel is cooled with phase-change materials (PV-PCM cooling systems). The conventional approach usually assumes one solid container filled with a PCM that is fixed into the backside surface of the PV panel to regulate the operating temperature of the PV panel. In the herein considered novel approach, instead of one PCM filled container, several smaller containers filled with PCM materials were used and experimentally tested to determine the performance benefit. The gained experimental results of the two different PV-PCM cooling configurations were compared with a referent PV panel. Based on the experimental results, it was found that the performance of the PV system (overall power yield), for the assumed measurement period, was improved for about 2.5% in the case of the concept with a full PCM container when compared to the referent PV panel. The proposed novel PV-PCM passive cooling approach, with several independent PCM containers, reached a performance improvement of 10.7%, which is considerably higher with respect to the usually applied concept with a full PCM container. The quantity of utilized PCM materials and aluminum, in several container configurations, was 47% (PCM) and 36% (aluminum) less, when compared with the passive cooling configuration with solid a PCM container. The revealed results indicated the potential of the novel proposed PV-PCM passive cooling approach regarding performance improvements and resource utilization, which would affect both economic and environmental aspects. Highlights: Two passive cooling configurations experimentally examined for photovoltaics. Passive techniques considered the use of a phase change material (PCM). Novel PV-PCM cooling approach tested. Highest performance improvement of 10.7% ensured by the novel approach. Reduction of main resource use by 47% (PCM) and 36% (aluminum).